DNA Identification of Fasciola spp. on human and cattle in Central Vietnam - The, Dang Tat; Hung, Le Quang; Hien, Cao Van (Academia Journal of Biology, 2015)
The comparison and analysis of the DNA sequence of two Fasciola samples collected from humans and four other Fasciola samples with different morphology collected from cows in Binhdinh province, to the homologous sequences of the nucleotide of other Fasciola from some countries in South Asia and around the world, shows that all Fasciola samples from both humans and cows are F.gigantica. For the first time, this Fasciola species is detected as endoparasites in humans in Vietnam. The F.gigantica population in Vietnam and some countries in South Asia except Indonesia have the relatively high structural homogentisic. The macroscopic observation of 1350 Fasciola specimens collected from humans and cattle in Binhdinh and Khanhhoa provinces identified three different morphological types of the body of F.hepatica, F.gigantica and the resemblance between F.gigantica and F.hepatica. Specified Polymerase Chain Reaction (PCR) shows that they are all F.gigantica. This means that F.gigantica has a high potential for morphological disguise, and that all sanples Fasciola detected in cattle from Binhdinh and Khanhhoa provinces are F. gigantica. It is possible that F. hepatica does not exist in this region. Also, based on the results of this study and the conflicting results before, existence of F. hepatica in Vietnam is still open to question. Furthermore, a variant of redia of F. gigantica with more cercaria than other common types was found from Lymnaea snails.